Modeling of masonry infilled RC frames with different aspect ratios using plastic hinge and equivalent strut - Ahmed M. El-Kholy; Sayed M. Sayed; Mohamed M. El-Assaly; Mohamed K. Ismail (Journal of Engineering and Applied Science)
Abstract The existence of diverse modeling approaches for masonry-infilled frames causes uncertainty among practicing engineers when seeking a definitive model for their design practice. This paper presents a practical and simple approach to modeling the masonry-infilled frames. The proposed approach models the plasticity in the beams and columns of the reinforced concrete (RC) frames using flexural plastic hinges while modeling the masonry panel as a nonlinear equivalent strut. The implementation of the hinge is based on discretizing the frame cross-section into fibers and utilizing a popular formula to estimate the plastic hinge length specific to masonry-infilled frames. Furthermore, the implemented equivalent strut model employs a trilinear force–displacement backbone curve. The efficiency of this approach was evaluated against the experimental results of four different tested infilled RC frames available in the literature. A conventional approach based on a typical explicit plastic hinge was included for comparison. Unlike the conventional approach, the numerical results obtained from the presented approach better matched the experimental results. Subsequently, the presented approach was utilized to investigate the effect of the aspect ratio of clay masonry infill panels on the behavior of RC frames. The investigation revealed that the panels with larger aspect ratios provided a larger contribution to the ultimate lateral load, despite experiencing lower ultimate axial stresses compared to panels with smaller aspect ratios. However, increasing the thickness of the masonry infill with a small aspect ratio appeared to improve its effectiveness in resisting the lateral force.